(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Corruption remains a highly complex problem in Indonesia, which has significant impacts on governance, economic development, and public trust. This article examines the dynamics of corruption in the Indonesian government through several corruption issues that occur and involve policy makers or government authorities. In addition, it also highlights the complexity of corruption, including the relationship between political influence, institutional weaknesses, and failures in the corruption prevention and handling system. Furthermore, this article further explores anti-corruption efforts in Indonesia, focusing on strategies such as the establishment of the Corruption Eradication Commission (KPK), legal reform, transparency initiatives, and community involvement. By conducting a critical analysis of the challenges in efforts to handle corruption in Indonesia, which are also related to political interference, institutional weaknesses, and cultural acceptance of corruption, as well as opportunities to strengthen anti-corruption measures in handling corruption.